2013
DOI: 10.1103/physrevd.88.024013
|View full text |Cite
|
Sign up to set email alerts
|

Three dimensional Eddington-inspired Born-Infeld gravity: Solutions

Abstract: Three dimensional Eddington-inspired Born-Infeld gravity is studied with the goal of finding new solutions. Beginning with cosmology, we obtain analytical and numerical solutions for the scale factor a(t), in spatially flat (k = 0) and spatially curved (k = ±1) Friedmann-Roberston-Walker universes with (i) pressureless dust (P = 0) and (ii) perfect fluid (P = ρ 2 ), as matter sources. When the theory parameter κ > 0, our cosmological solutions are generically singular (except for the open universe, with a spec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…For instance, the (2 þ 1)-dimensional Euclidean gravity coupled with a massless scalar field can be related to the (3 þ 1)-dimensional static spacetime [17]. Moreover, the (2 þ 1)-dimensional cosmology is a rather active topic both from classical and quantum perspectives [18][19][20][21]. The purpose of this paper is to make a first step to investigate the issue of the (2 þ 1)-dimensional LQC.…”
Section: Introductionmentioning
confidence: 97%
“…For instance, the (2 þ 1)-dimensional Euclidean gravity coupled with a massless scalar field can be related to the (3 þ 1)-dimensional static spacetime [17]. Moreover, the (2 þ 1)-dimensional cosmology is a rather active topic both from classical and quantum perspectives [18][19][20][21]. The purpose of this paper is to make a first step to investigate the issue of the (2 þ 1)-dimensional LQC.…”
Section: Introductionmentioning
confidence: 97%
“…More relevant studies can be found in Refs. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. It was shown in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…This gives a hint of having a wormhole geometry supported by ordinary matter, in EiBI gravity. Attempts have been made to construct a wormhole geometry in this modified gravity [24,26,27]. The authors in [24] obtained a wormhole geometry supported by pressureless dust, in three dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…Various aspects of EiBI gravity have been studied by many researchers in the recent past. Spherically symmetric solutions, cosmology, and astrophysical aspects have been worked out [15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%